Increased nitric oxide activity in a rat model of acute pancreatitis. Issue 4 (1st October 1998) - Al-Mufti, R A; Williamson, R C N; Mathie, R T
Abstract : Background —Overproduction of nitric oxide (NO) via induction of the inducible NO synthase (iNOS) is an important factor in the haemodynamic disturbances of several inflammatory states. Aims —To identify the role of NO in a caerulein induced model of acute pancreatitis in the rat. Methods —Arterial blood pressure and plasma NO metabolites were measured at zero and seven hours in adult male Wistar rats administered caerulein (n=10) or saline (n=10). Pancreatic activity of NOS (inducible and constitutive) was assayed biochemically. The pancreatic expression and cellular localisation of NOS and nitrotyrosine (a marker of peroxynitrite induced oxidative tissue damage) were characterised immunohistochemically. Results —Compared with controls at seven hours, the pancreatitis group displayed raised plasma NO metabolites (mean (SEM) 70.2 (5.9) versus 22.7 (2.2) μmol/l, p<0.0001) and reduced mean arterial blood pressure (88.7 (4.6) versus 112.8 (4.1) mm Hg, p=0.008). There was notable iNOS activity in the pancreatitis group (3.1 (0.34) versus 0.1 (0.01) pmol/mg protein/min, p<0.0001) with reduced constitutive NOS activity (0.62 (0.12) versus 0.96 (0.08) pmol/mg protein/min, p=0.031). The increased expression of iNOS was mainly localised within vascular smooth muscle cells (p=0.003 versus controls), with positive perivascular staining for nitrotyrosine (p=0.0012 versus controls). Conclusions —In this experimental model of acute pancreatitis, iNOS induction and oxidative tissue damage in the pancreas is associated with raised systemic NO and arterial hypotension. Excess production of NO arising from the inducible NO synthase may be an important factor in the systemic and local haemodynamic disturbances associated with acute pancreatitis.